Identification and characterization of S fimbria-binding sialoglycoproteins on brain microvascular endothelial cells. - Prasadarao, N V (1997)
We have previously shown that S-fimbriated Escherichia coli binds brain microvascular endothelial cells (BMEC) via a lectin-like activity of SfaS adhesin specific for NeuAc alpha2,3-galactose; however, BMEC molecules bearing these epitopes have not been identified. In the present study, we showed that the expression of S fimbriae conferred a three-fold increase in adhesion of E. coli to cow, human, and rat BMEC but did not enhance E. coli adhesion to systemic vascular endothelial cells such as human umbilical vein endothelial cells and human aortic arterial endothelial cells. Two BMEC-binding molecules for S fimbriae were identified as 65 (major)- and 130 (minor)-kDa sialoglycoproteins by S fimbria immunoblotting and were purified from bovine BMEC by wheat germ agglutinin and Maackia amurensis lectin (specific to NeuAc alpha2,3-galactose) affinity chromatography. The 65-kDa BMEC glycoprotein showed effective inhibition of S fimbria-mediated binding of E. coli to BMEC. Polyclonal antibodies raised against the mixture of 65- and 130-kDa proteins reacted to 65-kDa protein present only on BMEC, not on systemic vascular endothelial cells. Immunoprecipitation of biotinylated BMEC membrane proteins and immunocytochemistry studies of BMEC with anti-S fimbria-binding protein antibodies revealed that the 65-kDa protein is a surface protein. The N-terminal amino acid sequence of 65- and 130-kDa proteins showed no significant sequence homology with any other known proteins. These findings suggest that 65- and 130-kDa proteins represent novel sialoglycoproteins involved in the binding of S-fimbriated E. coli to BMEC.